PERBANDINGAN LAPORAN KEUANGAN PADA PT. KURNIA MUSTIKA KENCANA PLASTIK DENGAN ANALISIS DINAMIS - Nurul Latifah P. (STIE Pelita Nusantara Semarang, 2006)
Financial Statement is an important tool to get financial position and company's reward informations. Financial analysis relate financial statement subject with others and shows its trend. Financial Statement interpretation relate financial statement subject within result analysis and decision making. From this relation, we can value the company for decision making. With compare two or more Balance Sheet will knowed happened trends.